17-ß-Estradiol and Testosterone concentrations in claws of puppies up to 60 days of age (International Journal of Health, Animal Science and Food Safety, 2018)
IntroductionThe current 30% of canine perinatal mortality (Tonnessen et al., 2012) claims the need to deepen the knowledge about this phase, characterized by long-term hormonal and metabolic changes, that could benefit of long time-frame methods of investigation, reducing the quantity of samplings and respecting animal welfare (Veronesi et al., 2015). Therefore, blood, saliva, urine and feces, being invasive and providing punctual information, are not appropriate matrices.Given that sexual steroid hormones were reported to have an influence already from the perinatal period (Frey et al., 2017), in this work 17-β-Estradiol (E2) and Testosterone (T) concentrations were assessed from the claws of dogs up to 60 days of age. Material and MethodsTen male and 10 female puppies, viable and healthy, born by elective cesarean section, were enrolled. Samplings were performed by trimming claws at birth, and the regrowth at 30 and 60 days of age. Then, E2 and T concentrations were analyzed by RIA (Veronesi et al., 2015) and a possible effect of gender evaluated. ResultsAll the hormonal claws concentrations showed a significant (p
Keywords: Dog; Puppy; Claws; 17-ß-Estradiol; Testosterone